Problems of Turkish public administrative structure - Çakır, Cevdet Eray (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Public administration in Turkey has recently experienced a reformation period, in order to solve the inefficiency problem of its local governments caused by cultural and traditional understanding of unitary state, which is inherited to Turkish Republic from Ottoman Empire. The paper focuses on the problems of public administration of Turkey that directly caused reforms.
Keywords: public administration; administrative reforms; Turkish administrative structure